Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fphar.2021.732541
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Gut Microbiota in Patients with Overweight and Obesity with Dyslipidemia and its Responses to Long-term Orlistat and Ezetimibe Intervention: A Randomized Controlled Open-label Trial

Abstract: This study investigated the gut microbiota and short chain fatty acids (SCFAs) characteristics of subjects with obesity from Xinjiang in northwestern China, a region with a multiethnic culture and characteristic lifestyle, and to explore the potential microbes that respond to a 12-wk medication of orlistat and ezetimibe with a randomized controlled open-label trial manner. The gut microbiota profile of patients with overweight and obesity with dyslipidemia in Xinjiang was distinctive and characterized by enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 74 publications
3
24
0
Order By: Relevance
“…Studies have reported controversial data about the Firmicutes/Bacteroidetes ratio and the proportion of Firmicutes and Bacteroidetes in obesity. The present data were in agreement with many other studies in China [22], United Kingdom [23], and Canada [24] where insignificant differences in Firmicutes to Bacteroidetes ratio was observed between lean and obese individuals, other studies found that the gut microbiota of obese people is characterized by an increase in the Firmicutes/Bacteroidetes ratio; as in Ukraine [25] and Italy [26]; while others even find an opposite relationship; as in China [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studies have reported controversial data about the Firmicutes/Bacteroidetes ratio and the proportion of Firmicutes and Bacteroidetes in obesity. The present data were in agreement with many other studies in China [22], United Kingdom [23], and Canada [24] where insignificant differences in Firmicutes to Bacteroidetes ratio was observed between lean and obese individuals, other studies found that the gut microbiota of obese people is characterized by an increase in the Firmicutes/Bacteroidetes ratio; as in Ukraine [25] and Italy [26]; while others even find an opposite relationship; as in China [27].…”
Section: Discussionsupporting
confidence: 93%
“…Obese females in the present study had insignificant higher values of log Lactobacillus, and insignificant lower values of Bifidobacteria; than normal weight ones. Similarly, a study showed that microbiota composition of overweight and obese adults with dyslipideamia in China was characterized by over representation of Lactobacillus as a counter protective reaction but with reduction of Bifidobacterium [22]. It was also found that gut microflora in obese patients is characterized by greater numbers of Lactobacillus and lesser numbers of Bifidobacteria species [29].…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have also shown a similar trend in mice together with reduced microbial diversity and richness [8]. Evidence of increased Proteobacteria and decreased Alloprevotella associated with Orlistat therapy in humans has been reported [11].…”
Section: Introductionmentioning
confidence: 68%
“…Recent reports suggests that Orlistat therapy induces significant modifications to gut microbe population [8] with Actinobacteria and Proteobacteria groups shown to be the most affected. However, some studies suggest these changes were limited to Proteobacteria, a potential marker diagnostic marker of ecological imbalance and disease risk [9], and other bacterial populations of low relative abundance [10,11]. In our previous study, obese mice treated with a HFD underwent two different interventions [12].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation